2011
DOI: 10.1080/19393210.2011.585244
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons in Brazilian commercial soybean oils and dietary exposure

Abstract: In this study the 13 polycyclic aromatic hydrocarbons (PAHs) identified as being genotoxic and carcinogenic by the Joint FAO/WHO Expert Committee on Food Additives (JECFA) were determined in different brands of soybean oils available on the Brazilian market, totalling 42 samples. A solid-phase extraction (SPE) method for sample clean-up with a C18 cartridge, followed by reversed-phase HPLC with fluorescence detection, was used for determination. The method showed good recoveries for most PAHs studied with valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 22 publications
2
21
1
5
Order By: Relevance
“…The summed PAHs found for soybean oil in this study was very similar to those determined in commercial samples (10.4-112.0 lg/kg) by Camargo et al (2011b). PAHs profile in both studies is practically the same.…”
Section: Pahs In Oilssupporting
confidence: 79%
See 1 more Smart Citation
“…The summed PAHs found for soybean oil in this study was very similar to those determined in commercial samples (10.4-112.0 lg/kg) by Camargo et al (2011b). PAHs profile in both studies is practically the same.…”
Section: Pahs In Oilssupporting
confidence: 79%
“…A study conducted by Camargo, Antoniolli, Vicente, and Tfouni (2011b) showed relatively high and variable levels of PAHs in soybean oils commercially available in the Brazilian market. Thus, considering the importance of soybean oil in national diet, it is important to identify the main source of crude oils contamination by PAHs, be acquainted with the extension of this contamination and evaluate the possible influence of each step of the refining process on PAHs concentration decrease.…”
Section: Introductionmentioning
confidence: 99%
“…Lipophilic components were believed to be the major precursors of PAHs formed from a burning cigarette (McGrath, Jan, Wooten, Chan, & Hajaligol, 2007). On the other hand, in this study it is possible that the cooking oil used to marinade the beef samples has been contaminated with PAHs during the preparing process; the presence of PAHs in edible oils has been reported in some studies (Camargo, Antoniolli, Vicente, & Tfouni, 2011;Teixeira, Casal, & Oliveira, 2007).…”
Section: Recovery and Precision Studymentioning
confidence: 92%
“…In a study from 2011, 42 samples of soybean oil were analyzed for the presence of 13 PAH. In the results, individual PAH levels ranged from 0.2 to 26.1 µg/kg and summed PAH levels were up to 112.0 µg/kg [4].…”
Section: Introductionmentioning
confidence: 88%
“…Another source of PAH contamination in food is by deposition from the environment [1]. The presence of PAH have been reported in different types of food, such as soybean oil, bivalves, infant foods, vegetable and fruits [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%